PENGARUH KECERDASAN EMOSIONAL DAN KEPRIBADIAN TERHADAP KINERJA KARYAWAN PT. BNI SYARIAH BENGKULU - Lia Agustiana Sari; Onsardi Onsardi; Sri Ekowati (Yayasan Insani Mandiri Santani, 2020)
This study aims to determine the effect of emotional intelligence and personality on the performance of employees of PT. BNI Syariah Bengkulu. This study used a sample of 42 respondents. The technique of collecting data using a questionnaire. The analysis technique used is simple linear regression. This research uses validity test, reliability test, followed by hypothesis testing. Based on the results of multiple linear regression analysis, emotional intelligence and personality have a positive effect on employee performance (Y), this is evidenced by the regression equation Y = 7.14.210 + 0.269X1 + 0.821X2. As well as the coefficient of determination R square = 0.378, which means emotional intelligence and personality, contributed 37.8% to employee performance (Y) and 62.2% was influenced by other factors not explained in this study. From the results of hypothesis testing, emotional intelligence has a significant effect on employee performance. Personality has a significant effect on employee performance. From the results of the F test, emotional intelligence and personality have a significant effect on employee performance.